Comparison of Cell Wall Polysaccharide Composition and Structure Between Strains of Sporothrix schenckii and Sporothrix brasiliensis - Villalobos-Duno, Héctor L.; Barreto, Laura A.; Alvarez-Aular, Álvaro; Mora-Montes, Héctor M.; Lozoya-Pérez, Nancy E.; Franco, Bernardo; Lopes-Bezerra, Leila M.; Niño-Vega, Gustavo A. (Frontiers in Microbiology, 2021)
Sporothrix schenckii, Sporothrix brasiliensis, and Sporothrix globosa are the main causative agents of sporotrichosis, a human subcutaneous mycosis. Differences in virulence patterns are associated to each species but remain largely uncharacterized. The S. schenckii and S. brasiliensis cell wall composition and virulence are influenced by the culturing media, with little or no influence on S. globosa. By keeping constant the culturing media, we compared the cell wall composition of three S. schenckii and two S. brasiliensis strains, previously described as presenting different virulence levels on a murine model of infection. The cell wall composition of the five Sporothrix spp. strains correlated with the biochemical composition of the cell wall previously reported for the species. However, the rhamnose-to-β-glucan ratio exhibits differences among strains, with an increase in cell wall rhamnose-to-β-glucan ratio as their virulence increased. This relationship can be expressed mathematically, which could be an important tool for the determination of virulence in Sporothrix spp. Also, structural differences in rhamnomannan were found, with longer side chains present in strains with lower virulence reported for both species here studied, adding insight to the importance of this polysaccharide in the pathogenic process of these fungi.